Molecular Characterization of Glucose-6-Phosphate Dehydrogenase: Do Single Nucleotide Polymorphisms Affect Hematological Parameters in HIV-Positive Patients? - Kwabena Owusu Danquah; Kofi Mensah; Charles Nkansah; Samuel Kwasi Appiah; Mark Noagbe; Yasmine Hardy; David O. Ntiamoah; Lillian Antwi Boateng; Max Efui Annani-Akollor; Eddie-Williams Owiredu; Alexander Yaw Debrah; Otchere Addai-Mensah (Journal of Tropical Medicine)
This descriptive, cross-sectional study aimed at evaluating the prevalence of G6PD deficiency and the 376A ⟶ G, 202G ⟶ A single nucleotide polymorphisms (SNPs) among HIV patients attending care at a teaching hospital in Ghana and determine how the SNPs affect haematological profile in HIV. A total of 200 HIV-positive Ghanaians were recruited. Venous blood samples were obtained and complete blood count, and G6PD screening and genotyping for the 376A ⟶ G, 202G ⟶ A SNPs were performed. Out of the 200 participants, 13.0% (26/200) were G6PD-deficient based on the methemoglobin reductase technique, with 1.5% (3/200) and 11.5% (23/200) presenting with partial and full enzyme defect, respectively. Among the 13.0% participants with G6PD deficiency, 19.2% (5/26), 30.8% (8/26), and 19.2% (5/26) presented with 376A ⟶ G only (enzyme activity (EA): 1.19 U/g Hb), 202G ⟶A only (EA: 1.41 U/g Hb), and G202/A376 SNPs (EA: 1.14 U/g Hb), respectively. Having the 376A ⟶ G mutation was associated not only with lower red blood cell (RBC) count (3.38 × 106/µL (3.16–3.46) vs 3.95 × 106/µL (3.53–4.41), p = 0.010) but also with higher mean cell volume (MCV) (102.90 (99.40–113.0) vs 91.10 fL (84.65–98.98), p = 0.041) and mean cell haemoglobin (MCH) (33.70 pg (32.70–38.50) vs 30.75 pg (28.50–33.35), p = 0.038), whereas possessing the 202G ⟶ A mutation was associated with higher MCV only (98.90 fL (90.95–102.35) vs 91.10 fL (84.65–98.98), p = 0.041) compared to G6PD nondeficient participants. The prevalence of G6PD deficiency among HIV patients in Kumasi, Ghana, is 13.0% prevalence, comprising 1.5% and 11.5% partial and full enzyme defect, respectively, based on the methemoglobin reductase technique among HIV patients in Ghana. Among G6PD-deficient HIV patients, the prevalence of G202/A376 SNPs is 19.2%. The 376A ⟶ G mutation is associated not only with lower RBC count but also with higher MCV and MCH, whereas the 202G ⟶ A mutation is associated with higher MCV compared to the normal G6PD population.